Daya Hambat Ekstrak Buah Delima Merah (Punica granatum Linn) terhadap Pertumbuhan Staphylococcus aureus (The Inhibition of Red Pomegranate Fruit Extract (Punica granatum Linn) on The Growth of Staphylococcus aureus) - Erlita Prestiandari; Sri Hernawati; Leni Rohma Dewi (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Background: Staphylococcus aureus is the most common microorganism in angular cheilitis. Angular cheilitis is inflammation in one corner of the mouth or both corners of the mouth may extend involving the lips commisura and surrounding skin. The prevalence of angular cheilitis is 0.2-15.1% in children and 0.7-3.8% in adults. One of alternative treatment by using herbal plants, namely red pomegranate. Red pomegranate contains flavonoids, tannins, and alkaloids as antibacterial. Objective: to determine the inhibition of red pomegranate extract on growth of Staphylococcus aureus. Methods: disk diffusion method with 6 samples in each study group. The study group consisted of 4 treatment groups (25%, 50%, 75% and 100% red pomegranate extract), positive control group (fusidic acid), and negative control group (sterile aquades). Data were analyzed using One Way Anova test and LSD (Least Significant Difference) test. Results and conclusions: red pomegranate extract has the ability to inhibit the growth of Staphylococcus aureus. The concentration of red pomegranate extract has the greatest inhibitory effect on S. aureus growth, that is 75% and 100%. Keyword: Antibacterial activity, red pomegranate fruit extract, Staphylococcus aureus, disk diffusion method